Analysis of The Influence of Direct Marketing and Brand Image on Purchasing Decisions and Consumer Loyalty of 500 ml Sweet Condensed Milk of The Bagus Brand at PT. Riau Food Lestari Pekanbaru - ,; ,; ,; , (International Conference on Business Management and Accounting, 2025)
This research aims to determine and analyze the influence of direct marketing and brand image on purchasing decisions and consumer loyalty of 500 Ml Brand Bagus sweetened condensed milk at PT. Riau Food Lestari. The population in this research is consumers who shop at PT. Riau Food Lestari is spread and the exact number is not known. Furthermore, sampling in this research used the Roscoe approach which resulted in 120 respondents and was determined using the accidental sampling method. Data analysis in this research uses the second-generation multivariate data analysis method, namely SEM or Structural Equation Model. Based on the results of the research conducted, the results showed that direct marketing has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, direct marketing has a positive and significant effect on consumer loyalty, brand image has a positive and significant effect on consumer loyalty, and purchasing decisions have a positive and significant effect on consumer loyalty of 500 Ml Good Brand sweetened condensed milk at PT. Riau Food Lestari.